Location site of lanthanides in ZnO - Otal, Eugenio Hernan (2009)
Zinc oxide (ZnO) is a well-known wide-band-gap semiconductor material which has applications in UV light emitters [1], ozone sensors [2], cold field electron emitters [3], transparent electrodes[4], and piezoelectric devices[5]. Otherwise rare earth doped nanometric materials adquired an increased interest in the field of optical communication, phosphors, photonic crystals and displays. Recently, erbiumdoped ZnO has demonstrated to be a promising material in optical telecommunication applications. Erbium-doped ZnO has been prepared by laser ablation [6], ion implantation [7], electrochemical precipitation [8] and e-beam evaporation [9], In this project soft chemistry routes [10], were used to obtain nanocristalline ZnO with erbium as doping element. As properties of doped materials depend on location site of the doping element in host structure, EXAFS measurements were performed in order to obtain this information. Coordination number and neighbors distance can be determined by modeling and fitting of EXAFS signal, whereas site symmetry can be determined by the analysis of the XANES region.